The relationship between catchment characteristics and lake chemistry in the Republic of Ireland - Free, Gary N. (Trinity College (Dublin, Ireland). Department of Botany, 2002)
The purpose of this thesis was to examine the relationships between catchment characteristics and lake chemistry in the Republic of Ireland. Additional aims were to examine the seasonal variation in water chemistry and, where possible, variation over a period of years. The impetus for this research came from draft work on the European Union’s Water Framework Directive which currently requires catchment information to be used for the definition of lake types, risk assessment, and the design of monitoring programmes. Thirty-one lakes were sampled monthly or approximately quarterly during 1996 and 1997. This sample contained a wide range of the types of catchments and lakes found in Ireland. In addition, a more limited suite of information on 189 lakes and catchments was examined. Estimates were produced for export of the major ions Na+, Cl-, K+, Mg 2+, Ca 2+ and SO 2-/4. The principal catchment influences on export were rock type, deposition of marine salts and agricultural practices. Sodium and chloride had a curvilinear decline from the west coast indicating that aerosol deposition of sea-salts was an important factor. Examining export rates led to the discovery of a good curvilinear fit whereas previous work that used concentration found only an approximate trend. A highly significant relationship between fertiliser application and non-marine export indicted that agricultural practices were an important controlling factor. The similarity of the Cl- to SO 2-/4 ratio between atmospheric deposition and export indicated that SO 2-/4 inputs and outputs were in balance with the exception of lakes in Cavan and Monaghan where SO 2-/4 export was substantially higher than atmospheric deposition.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin